A Serological Survey of Cystic Echinococcosis in Equids in East of Turkey - Balkaya, I.; Simsek, S. (Iranian Scientific Society Medical Entomology, 2011)
Background: Cystic echinococcosis (CE), caused by hydatid cysts, is a widespread and hazardous disease in humans and animals worldwide. The disease is very common in Turkey, causing serious economic losses and public health problem. In this study, the seroprevalence of equine CE was determined by enzyme-linked immunosorbent assay (ELISA). Methods: Partially purified cyst fluid antigen from sheep hydatid cyst fluid was used as antigen in ELISA. A total of 250 equids consisting of 206 donkeys and 44 horses from various regions of Erzurum province of Eastern Turkey. Results: Anti- Echinococcus granulosus antibodies were detected in 78 (31.2%) of 250 equids. The prevalence rate was 20.4% for horses and 33.5% for donkeys. There was no statistically difference between sex and ages groups for both horses and donkeys (P>0.05). Conclusion: Equine CE is quite endemic in Eastern Turkey. The high prevalence of CE suggests that equids in the transmission cycles is possible as a source of infection for definitive hosts.
Keywords: Cystic echinococcosis; Donkey; Horse; ELISA; Seroprevalence; Turkey